Visual analysis of soil structure quality with different systems of use and management in Marajó, Municipality of Breves, Pará State, Brazil (Research, Society and Development, 2020)
The concept of soil quality is recent and has been used to evaluate the sustainability of different soil management practices. Visual assessment is an efficient, practical and simple tool for determining soil quality. The objective of the present work was to identify, through the visual field method, the structural quality of soils with different soil use and management systems in the Breves, PA region. The soil uses compared and used in this work were: an area with açai cultivation, an area with maize cultivation, soil area under fallow vegetation, and a contiguous area with forest fragment (native forest), as a quality reference soil structure. The evaluations were carried out with the aid of the visual assessment chart of the soil structure. The classification was based on the final result according to five visual scores for structural quality (Qe), being: Qe = 1 (better structural quality) and Qe = 5 (worse structural quality). High values for Qe are indicative of deterioration of soil structural quality. It is important to note that scores between 1 and 3 are indicative of acceptable management conditions and physical soil quality. It was possible to observe the visual differences of quality of soils, making possible to identify the different forms of structuring in function of the management. The area under native vegetation expresses higher soil quality by the evaluated visual indicator, when compared to the other environments, followed by the acreage, under fallow vegetation and cassava cultivated with corn. From the results obtained it was possible to observe that the visual quality index is a simple and effective practical method to differentiate the quality of the soil submitted to different uses and that the agricultural activities diminish the visual quality of the soil.